Tradisi kosi adat pernikahan di desa duria kecamatan lolofitu moi kabupaten nias barat - Fidelis Waruwu; Adrianus Bawamenewi; Anugerah Tatema Harefa; Amstrong Harefa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This research aims to (1) find out the implementation of the Kosi Traditional Wedding Tradition, (2) the factors that cause the younger generation to not care about the Kosi Traditional Wedding Tradition and (3) efforts to preserve the Kosi Traditional Wedding Tradition in the Duria Village Community, Lolofitu Moi District. The type of research uses a qualitative research method. Data collection instruments are observation, interview sheets and documentation. The results of field research: (1) indicate that the kosi tradition of traditional weddings in Duria Village is still practiced today, although it has undergone adjustments to reflect the changing times and socio-economic conditions of the community. The kosi tradition is carried out when a person is about to get married and aims to help the groom prepare for the wedding. The kosi gifts include money, rice, livestock such as pigs, building materials, and other valuables. This tradition reflects the values ​​of mutual cooperation and social cooperation that are still alive in the Duria Village community. (2) Factors that cause the low level of concern among the younger generation towards the kosi tradition of traditional weddings are caused by several factors, including the influence of modernization, technological developments, changes in mindsets, and a lack of understanding of the meaning and cultural values ​​contained in the kosi tradition. The younger generation tends to know the kosi tradition only in general as a form of mutual assistance, but does not yet understand in depth the social function, values ​​of responsibility, and the meaning of family contained within it. (3) Efforts to preserve the kosi wedding tradition are essential to prevent it from disappearing amidst the tide of social change. Preservation efforts can be carried out through the active involvement of traditional leaders, village government, the community, and the younger generation. These efforts include cultural education, traditional deliberations, sharing real-life experiences about the kosi tradition, and adapting the implementation of the tradition to avoid burdening the community. With these steps, it is hoped that the kosi tradition can continue to be preserved as a cultural heritage that holds social, cultural, and moral value for the Duria Village community